Seed banks of upper-montane areas, under post-disturbance restoration process, in "Planalto Sul Catarinense" region - Duarte, Edilaine (2022)
We aimed to verify the floristic-structural composition of regenerative seedlings of seed banks from areas under anthropic post-disturbance restoration process, in “Planalto Sul Catarinense” region, upper-montane environments. In each of three sites (Area 1, 2 and 3) at São Joaquim National Park, protected for almost ten years, but with different land-use history, we allocated one 20 x 100 m transect, sub-divided in 20 plots, where a total of 60 samples of soil and litter were collected. While the Areas 1 (A1) and 2 (A2) were originally covered by natural forest, the Area 3 (A3) can be considered as cattle raising grassland. In a greenhouse, all the collected material was submitted to the same procedure, with daily sprinkler irrigation. After the seed germination in trays, we performed a monthly qualitative and quantitative evaluation of emergent seedlings that were identified and classified according to origin (native and exotic) and life form. In one year, 5,604 seedlings were counted, belonging to 62 taxa. There was predominance of herbs (74.2%) and native species (67.7%), being Cyperus odoratus L. and Juncus capillaceus Lam. the most abundant. When compared to the original grassland area, those originated from past deforestation showed a greater species and life form heterogeneity as well as greater seedling density emergence from the collected seed bank. We concluded that the studied seed banks have the potential to support a prompt seedling colonization after disturbances, ensuring the soil cover, and thus, the necessary initial support for the advance of successional dynamics.